The sociolinguistics of narrative - Thornborrow, Joanna, 1957-; Coates, Jennifer, 1942- (Studies in narrative ;, 2005)
This book aims to appraise sociolinguistic work devoted to the form and function of storytelling and to examine in detail the ways in which narrative constitutes a fundamental discursive resource across a range of contexts. The chapters presented here bring together some of the most recent work in the theory and practice of narrative analysis from a broad sociolinguistic perspective. They address some of the questions left implicit whenever stories are brought within the analytic frame of sociolinguistics: What exactly do we mean by 'story'?; what kind of social and contextual variations can d.